Rosuvastatin suppresses atrial tachycardia-induced cellular remodeling via Akt/Nrf2/heme oxygenase-1 pathway. (May 2015) - Yeh, Yung-Hsin; Kuo, Chi-Tai; Chang, Gwo-Jyh; Chen, Ying-Hwa; Lai, Ying-Ju; Cheng, Mei-Ling; Chen, Wei-Jan
Abstract: Atrial fibrillation (AF) is associated with structural remodeling in atrial myocytes. Emerging evidence suggests that statin has a protective effect on AF through cholesterol-independent mechanisms. The aim of this study is to investigate whether heme oxygenase-1 (HO-1), a potent antioxidant system, mediates the suppressive effect of statin on atrial tachycardia-induced structural remodeling. Treatment of cultured atrium-derived myocytes (HL-1 cell line) with rosuvastatin enhanced HO-1 expression/activity and attenuated tachypacing-induced oxidative stress and myofibril degradation. Heme oxygenase-1 inhibitors and small-interfering RNA for HO-1 blocked the inhibitory effect of rosuvastatin on tachypacing-stimulated changes, suggesting the crucial role of HO-1 in mediating the effect of rosuvastatin. Time-dependent experiments and loss-of-function study demonstrated that Akt/Nrf2 pathways lay to the up-stream of HO-1 in this signaling cascade. Furthermore, the involvement of Akt/Nrf2/HO-1 pathway in the antioxidant effect of rosuvastatin was documented in an ex vivo tachypacing model. The suppressive effect of statin on atrial tachypacing-induced cellular remodeling is mediated via the activation of Akt/Nrf2/HO-1 signaling, which provides a possible explanation for the protective effect of statin on AF. Highlights: Statin treatment enhanced heme oxygenase-1 expression either in cultured atrial myocytes or in vivo. Heme oxygenase-1 mediated the suppressive effect of statin on atrial tachycardia-induced structural remodeling. Akt/Nrf2 pathways lay to the up-stream of heme oxygenase-1 in operating statin effect.